Bibliography of Antarctic Paleobotany and Palynology - Taylor, Edith L.; Taylor, Thomas N. (Byrd Polar Research Center, The Ohio State University., 1988)
This bibliography was prepared for participants of the Workshop on Antarctic Paleobotany and It's Relationship to Reconstructions of Gondwana, which was held at the Ohio State University on June 12-15, 1988. These references represent part of a larger bibliography of Gondwana paleobotany ard palynology. This bibliography strives to include all papers that describe paleobotanical finds in Antarctica or that review those finds. All the paleobotanical entries that include "Antarctica" within the subject headings either mention fossil plants found on the continent or include descriptions of floras, etc. Some additional papers on southern hemisphere floras and reconstructions of Gondwana have been included, but no attempt has been made to completely cover the literature in these areas. Because of the scattered nature of the literature on Antarctic research, there are no doubt references to fossil plants that are not included in this bibliography. National Science Foundation